Performance of the MGIT TBc identification test and meta-analysis of MPT64 assays for identification of the Mycobacterium tuberculosis complex in liquid culture. - Brent, A; Mugo, D; Musyimi, R; Mutiso, A; Morpeth, S; Levin, M; Scott, J (2011)
Rapid MPT64-based immunochromatographic tests (MPT64 ICTs) have been developed to detect Mycobacterium tuberculosis complex (MTBC) in culture. We demonstrated the noninferiority of one commercial MTP64 ICT, the MGIT TBc identification (TBcID) test, to GenoType line probe assays for MTBC identification in positive MGIT cultures. Meta-analysis of MPT64 ICT performance for identification of MTBC in liquid culture confirmed similar very high sensitivities and specificities for all three commercial MPT64 assays for which sufficient data were available.